Pengaruh Perencanaan Pajak, Free Cash Flow, Sales Growth dan Kepemilikan Manajerial Terhadap Manajemen Laba Pada Perusahaan Properti dan Real Estate : (Yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2020-2023) (Jurnal Kendali Akuntansi, 2025)
This study is motivated by the importance of financial report transparency in property and real estate companies, particularly regarding earnings management practices that may affect the quality of information for stakeholders. The purpose of this research is to analyze the effect of tax planning, free cash flow, sales growth, and managerial ownership on earnings management in property and real estate companies during the 2020–2023 period. The method employed is a quantitative approach using multiple linear regression analysis with SPSS Version 29. The research sample consists of 21 companies over four years of observation, resulting in 84 financial reports as the research data. The analysis results indicate that sales growth and free cash flow have a positive influence on earnings management, whereas tax planning and managerial ownership show no significant effect. This study confirms that internal factors such as sales performance and cash flow management are more dominant in influencing earnings management compared to ownership aspects or tax strategies. Therefore, companies are advised to focus more on operational efficiency and cash flow management, as well as to enhance governance quality to minimize earnings management practices.